Exploring Teachers' Belief toward Teaching Language Features of Genres on K13 Curriculum - Ahmat Rondi Toyib; Achmad Anang Darmawan (STKIP AL HIKMAH SURABAYA, 2020)
The objectives of this research are to reveal the teachers’ point of view, describe the teachers’ practices, and to investigate the factors which influence teachers’ beliefs toward teaching language features of genres on K13. The research method used in this research is descriptive using qualitative approach. The procedures of the research were using four steps, such as pre-research, data collection, data analysis, and writing a report. The subjects of the research were three English teachers from the same school who are teaching in SMPN 21 Surabaya at the 7th and 8th grades using K13. The researcher conducted three steps in collecting data, such as observations, interviews, documentation. The result of the research are the teachers believed that they have to teach language features of genres to their students, drilling is still relevant to be applied, the way of teaching was adjusted due to the condition of the classroom. In their teaching and learning process, all teachers were teaching language features of genres using conventional ways, such as the teachers were only using a textbook as the main guidance in teaching, the teachers were handling all the learning activities, and the teachers did not guide the students to reflect what they had learned in that day as the goal of the implementation of K13. Then, that all teachers’ teaching practices were consistent to their beliefs were influenced by their experience as language learners, experience of what works best, personality factors, and principles derived from an approach or method.